PEMANFAATAN LIMBAH DARAH SAPI DAN KIAMBANG SEBAGAI PUPUK RAMAH LINGKUNGAN UNTUK MENDUKUNG PERTANIAN LAHAN GAMBUT YANG BERKELANJUTAN - ERNAWATI, HASTIN; CHOTIMAH, NUR CHUSNUL; KRESNATITA, SUSI; ICHRIANI, GUSTI IRYA (Buletin Udayana Mengabdi; Vol 14 No 1 (2015): April 2015)
ABSTRACT A Farming system adopted by farmers in Sub-District Kalampangan is very dependent agricultural systems with in organic fertilizer. The use of in organic fertilizers continuously providea considerable impact on the surrounding environment. Nutrient the soilare bound by the molecules of chemical fertilizers so the top soi lregeneration process can not to be done.One alternativesolutionthat is proposed is the use of fertilizers derived from local resources around, the cow blood waste from slaughter houses and swamp plant sgiant salvinia (Salvinia molesta). Trouble shooting methods in this service activities were 1) education and training composting of cow blood-giant salvinia 2) demonstration plot to show the prove of greatness of cow blood-giant salvinia compost to the plants 3) mentoring and coaching partner farmers. The results showed that cow blood and giant salvinia potentially be usedas contained in an environmentally friendly organic fertilizer fo able crops grownon peat. Thefertilizershould be developedso thatfarmerscanbea superior productin order to meetone of thecomponents neededto initiate thechangefromconventional farming systemstoorganic farming systems. Keywords : cow blood waste, giant salvinia, compost, organic fertilizer, organic farming